Local Champion: Communication Characteristics in Community Empowerment Based on Local Innovation - Didiek Tranggono; Praja Firdaus Nuryananda; Andre Yusuf T. Putra (Universitas Islam Balitar, 2021)
This research is focusing on the community development and empowerment in underdeveloped villages of Trenggalek regency by focusing on strengthening role of local champions in each village. The result from this study was the villages were villages with IDT (Inpres Desa Tertinggal) and IDB (Inpres Desa Berkembang) status, the consequence of which was often to get assistance from the government.Yet, not all of the villages were successful in optimizing government assistances. Tasikmadu, Winong, and Tegaren were the examples of successful villages in stepping up from underdevelop to developing villages. This qualitative study used focus group discussion and in-depth interview in order to get genuine data from local people. The data was not taken for granted, but verified by check-crossing from one local spot to another local spot. In sum, the application on the empowerment of underdeveloped rural communities is strongly supported by strengthening role of local champions from each village. Local champions act as driving forces to support the community in increasing their ability to get out of poverty